Revisiting Inclusion: An Exploration of Refugee-Led Education for Children with Special Educational Needs and Disabilities in Lebanon - Elnaz Safarha; Zeena Zakharia (Social Sciences)
This article explores the concept of inclusive education in contexts of forced displacement, where refugeehood intersects with special educational needs and disabilities (SEND), as well as gender, poverty, and overlapping forms of discrimination. Drawing on extensive engagement with a refugee-led, non-formal educational organization in Lebanon, we revisit inclusion for refugee children with SEND through a bottom-up lens. We consider inclusion within Lebanon’s sociopolitical landscape, focusing on a community of educators, most of whom are refugees themselves. Grounded in decolonial feminist epistemologies and critical refugee studies, we highlight the role of educators as cultural actors who employ engaged pedagogies to humanize the educational experiences of refugee children with SEND. By challenging traditional top-down, outcome-oriented policies that focus solely on structural access, this paper advocates for an alternative framework based on refugee educators’ orientations to working with children with SEND. This framework prioritizes holistic, context-sensitive approaches to inclusion and underscores the importance of humanizing education for refugees.